Testing for Equilibrium Multiplicity in Dynamic Markov Games - Taisuke Otsu; Martin Pesendorfer; Yuya Takahashi (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
This paper proposes several statistical tests for finite state Markov games to examine the null hypothesis that the data are generated from a single equilibrium. We formulate tests of (i) the conditional choice probabilities, (ii) the steady-state distribution of states and (iii) the conditional distribution of states conditional on an initial state. In a Monte Carlo study we find that the chi-squared test of the steady-state distribution performs well and has high power even with a small number of markets and time periods. We apply the chi-squared test to the empirical application of Ryan (2012) that analyzes dynamics of the U.S. Portland Cement industry and test if his assumption of single equilibrium is supported by the data.
urn:nbn:de:bvb:19-epub-17287-4
Keywords: C12; C72; D44; 330; Dynamic Markov Game; Multiplicity of Equilibria; Testing